2015
DOI: 10.1038/cdd.2014.234
|View full text |Cite
|
Sign up to set email alerts
|

USP11-dependent selective cIAP2 deubiquitylation and stabilization determine sensitivity to Smac mimetics

Abstract: Given their crucial role in apoptosis suppression, inhibitor of apoptosis proteins (IAPs) have recently become attractive targets for cancer therapy. Here, we report that cellular IAP2 (cIAP2) is specifically stabilized in several cancer cell lines, leading to resistance to Smac mimetics, such as BV6 and birinapant. In particular, our results showed that cIAP2 depletion, but not cIAP1 depletion, sensitized cancer cells to Smac mimetic-induced apoptosis. Ubiquitin-specific protease 11 (USP11) is a deubiquitylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 65 publications
6
41
1
Order By: Relevance
“…The in vitro deubiquitination assay was performed as described previously . Briefly, ubiquitinated Flag‐ULK1, Flag‐USP20 wild‐type (WT), and Flag‐USP20 catalytically inactive (CI) proteins were isolated from HEK293 cells transiently expressing Flag‐ULK1 and HA‐Ub, the plasmid encoding Flag‐USP20 wild‐type (WT) alone, and plasmid encoding the Flag‐USP20 catalytically inactive (CI) form alone, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro deubiquitination assay was performed as described previously . Briefly, ubiquitinated Flag‐ULK1, Flag‐USP20 wild‐type (WT), and Flag‐USP20 catalytically inactive (CI) proteins were isolated from HEK293 cells transiently expressing Flag‐ULK1 and HA‐Ub, the plasmid encoding Flag‐USP20 wild‐type (WT) alone, and plasmid encoding the Flag‐USP20 catalytically inactive (CI) form alone, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…cIAP expression is known to be regulated at the transcriptional, translational, and post-translational levels [2931]. This study for the first time demonstrated that cIAP2 is directly stabilized through Pellino-1-mediated Lys63-polyubiquitination.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, a mass of work concentrated on the key mechanisms of therapeutic resistance to SMs in cancer cells. Previous studies confirmed that some cancer cells evade SM-induced cell death via stabilization of cIAP2 [85][86][87]. Some resistant cell lines have such an intense tendency to upregulate cIAP2, while sensitive cells seem to be less susceptible to signals that upregulate cIAP2.…”
Section: Mechanism Of Action Of Smsmentioning
confidence: 79%
“…In the absence of cIAP1 or TRAF2, the newly generated cIAP2 is no longer downregulated by SMs. Another report showed that overexpression of ubiquitin-specific protease 11 (USP11) led to stabilization of cIAP2 and promoted SM therapeutic resistance [86].…”
Section: Mechanism Of Action Of Smsmentioning
confidence: 99%